Relationships between functional movement quality and sports performance in elite figure skating athletes of China - Liu, Z.; Dai, J.; Yang, R.; Yue, L.; Guo, C.; Yin, J. (The Journal of Strength and Conditioning Research, 2024)
This study aimed to determine the optimal functional movement screen (FMS) cut score for assessing the risk of sports injuries and to explore the correlations between functional movement quality and sports performance among elite figure skaters. A total of 22 elite figure pairs skaters in China underwent FMS, sports performance, and clinical examinations for sports injuries. The FMS cut score was determined using the receiver operating characteristic curve. Pearson's rank correlation analysis was used to quantify associations between the variables. (a) The optimal FMS cut score for assessing the risk of sports injuries was 13 (p = 0.008), with an area under curve of 0.838. The sensitivity and specificity were 0.889 and 0.692, respectively. (b) The trunk stability push-up (TSPU), an individual FMS test, predicted injuries in figure skaters (p = 0.015). (c) Moderate correlations were found between shoulder mobility and bench strength (r = -0.453, p = 0.034), counter movement jump (r = -0.582, p = 0.007), and 30-m sprint (r = 0.567, p = 0.009). A strong correlation was observed with squat jump (r = -0.774, p = 0.001). In addition, TSPU scores moderately correlated with 30-m sprint times (r = -0.511, p = 0.021) and 30-s average anaerobic power (r = 0.503, p = 0.024). These findings indicate that both the FMS total score =13 and the FMS individual score serve as indicators of injury risk in figure skaters. However, only the FMS individual score reflected the sports performance. This likely results from the similarity in kinetic chain systems and movement patterns involved in both the FMS individual test and sports performance, suggesting a promising assessment strategy for sports performance.